2019
DOI: 10.1097/qai.0000000000001992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV Subtype and Antiretroviral Therapy on HIV-Associated Neurocognitive Disorder Stage in Rakai, Uganda

Abstract: Background: Combination antiretroviral therapy (ART) improves HIV-associated neurocognitive disorder (HAND) stage in the United States where subtype B predominates, but the effect of ART and subtype on HAND stage in individuals in Uganda with subtypes D and A is largely unknown. Setting: A community-based cohort of participants residing in Rakai, Uganda. Methods: Three hundred ninety-nine initially ART-naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The proportion of cases in this study with impairment based on individual tests or domain T-scores (17-23%) is in line with our previous findings (Kanmogne et al, 2018;Kanmogne et al, 2010;Njamnshi et al, 2009;Njamnshi et al, 2008) and some previously reported prevalence of HAND in Nigeria (21.5%) (Yusuf et al, 2017) and South Africa (23%) (Joska, Fincham, Stein, Paul, & Seedat, 2010). However, these are much lower than HAND prevalence reported among HIV-infected adults in other studies in Nigeria, China, and India (26-28%) (Jumare et al, 2019;Royal et al, 2012); South Africa (36-53%) (Joska et al, 2011;Mogambery, Dawood, Wilson, & Moodley, 2017), Botswana (37-38%) (Lawler et al, 2011), Zambia (34-35%) (Kabuba et al, 2017), Uganda (38-64%) (Nakku, Kinyanda, & Hoskins, 2013;Sacktor et al, 2019;Yechoor et al, 2016), and the United States (36-45%) (Heaton et al, 2015). Test instruments used in these studies varied from simpler International HIV Dementia Scale to more complete NP batteries, and such differences could have played a role in the wide variations in HAND prevalence observed across studies.…”
Section: Discussionmentioning
confidence: 82%
“…The proportion of cases in this study with impairment based on individual tests or domain T-scores (17-23%) is in line with our previous findings (Kanmogne et al, 2018;Kanmogne et al, 2010;Njamnshi et al, 2009;Njamnshi et al, 2008) and some previously reported prevalence of HAND in Nigeria (21.5%) (Yusuf et al, 2017) and South Africa (23%) (Joska, Fincham, Stein, Paul, & Seedat, 2010). However, these are much lower than HAND prevalence reported among HIV-infected adults in other studies in Nigeria, China, and India (26-28%) (Jumare et al, 2019;Royal et al, 2012); South Africa (36-53%) (Joska et al, 2011;Mogambery, Dawood, Wilson, & Moodley, 2017), Botswana (37-38%) (Lawler et al, 2011), Zambia (34-35%) (Kabuba et al, 2017), Uganda (38-64%) (Nakku, Kinyanda, & Hoskins, 2013;Sacktor et al, 2019;Yechoor et al, 2016), and the United States (36-45%) (Heaton et al, 2015). Test instruments used in these studies varied from simpler International HIV Dementia Scale to more complete NP batteries, and such differences could have played a role in the wide variations in HAND prevalence observed across studies.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to improving performance in tests of fine motor functions and speed of mental processing, ART use is also associated with improved performance in NP tests assessing concentration, memory and mental flexibility 5 ; and treatment failure is associated with poor performance on NP tests 9 . Despite these positive effects of ART on performance on some NP tests and the fact that ART use is associated with decreased prevalence of HAD, the overall prevalence of HAND in the current ART era remains high 5,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies have shown that the odds of neurocognitive impairment increased in subjects with high plasma viral loads (VL) 10 and that such impairment is associated with poor health-related quality of life 11 . Although the prevalence of HIV-associated dementia (HAD), the most severe form of HAND, has markedly decreased in the current ART era 5 , 12 , 13 , milder forms of HAND [asymptomatic neurocognitive impairment and mild neurocognitive disorders] and overall neurocognitive impairment still occur in up to 50% of HIV-infected persons 13 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographically adjusted normative data were obtained from 400 HIV‐negative healthy Ugandan adults [43]. Neurocognitive data from every participant were adjusted for age and education, as described previously [44].…”
Section: Methodsmentioning
confidence: 99%